1996
DOI: 10.1136/bmj.312.7047.1633
|View full text |Cite
|
Sign up to set email alerts
|

Survival of 1476 patients initially resuscitated from out of hospital cardiac arrest

Abstract: About 40% of initial survivors of resuscitation out of hospital are discharged home without major neurological disability. Patients at high risk of subsequent cardiac death can be identified and may benefit from further cardiological evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(50 citation statements)
references
References 26 publications
3
46
0
1
Order By: Relevance
“…9,10 Several investigators have recently evaluated the outcomes or quality of life of survivors of out-of-hospital cardiac arrest. [11][12][13][14] We have previously found that most patients who survive to hospital discharge have quite good quality of life and functional status. 15 Little is known, however, about the factors that may correlate with or lead to better functional status for these cardiac arrest survivors.…”
mentioning
confidence: 99%
“…9,10 Several investigators have recently evaluated the outcomes or quality of life of survivors of out-of-hospital cardiac arrest. [11][12][13][14] We have previously found that most patients who survive to hospital discharge have quite good quality of life and functional status. 15 Little is known, however, about the factors that may correlate with or lead to better functional status for these cardiac arrest survivors.…”
mentioning
confidence: 99%
“…consider it important, for the accuracy of clinical status of the patient, to evaluate the physician's long-term contact with the patient from the institution of CPR in the field to outpatient follow-up. Geographically, long-term studies include localities mainly in the United States of America and Europe (Denmark, Sweden, Norway, Estonia, the Netherlands, Scotland and Northern Ireland) (3)(4)(5)9,11,(16)(17)(18)(19). Data for our study were obtained from the region of East Bohemia in the Czech Republic.…”
Section: Discussionmentioning
confidence: 99%
“…In our file, 79% of patients survived in the first year, 72% of patients in the third year, and 62% in the fifth year regardless of the initial cardiac rhythm. Data from other authors on survival in the first year range between 76 to 88%, (3)(4)(5)17,19,22) in the third year between 67 to 81% (4,5,17,22,23) and in the fifth year between 41 to 77%. (4,5,7,22,23) In our study, 59% of patients survived seven years after OHCA.…”
Section: Causes Of Deathmentioning
confidence: 99%
See 2 more Smart Citations